Performance of shell and tube heat exchangers with varying tube layouts (2016)
Shell and tube heat exchangers (STHEs) are the most common type of heat exchangers and are applicable for wide range of operating temperatures and pressures. Numerical analyses on thermalhydraulic performance of three sets of shell and tube heat exchangers (STHEs) with different geometrical tube layout patterns variations namely; triangular (30º, STHE_T), rotated triangular (60º, STHE_RT) and the combined (STHE_C) patterns were carried out in this study. The results from solving the governing continuity, momentum and energy equations showed that bulk of the heat transfer and pressure drop occur during the cross-flow of shell-fluid through the tube bundles. Evaluation of the performances of the heat exchangers showed that the STHE_T is more desirable followed by the STHE_C as they exhibit higher heat transfer coefficient than the STHE_RT for the same pressure drop in the shell-side.